Axial current in the Dirac fiel - Villegas Silva, Fulgencio (2013)
This paper analyzes the current or current axial chiral Dirac field testing it introduces the term chiral Dirac equations directly and conjugated in order to find the chiral current as a function of particle mass involved. Determines that the condition that the axial current density is maintained is that the mass of the particle involved is nil or negligible.